Critical values of cyber parameters in a dynamic microgrid system - Lung‐An Lee (Wiley, 2022)
Abstract An islanded microgrid is cyber‐physical system, and the control relies on the communication system significantly. Improper parameters of the cyber system can result in instability of a microgrid system. To evaluate the impact of a networked control system on control performance, a cyber model is developed to represent data acquisition periods and communication delays. Simplification of the networked control system model is proposed to enhance the computational performance, making the analytical method applicable for large‐scale systems. Based on the analysis, a two‐dimensional stability region of a microgrid in the space of cyber parameters can be obtained. To validate the proposed method, a microgrid control scheme is proposed for power dispatch and regulation based on the droop and proportional‐integral (PI) feedback control. The analytical method is compared to the time‐domain simulation, and it is shown that the stability regions are nearly identical. The critical values of cyber parameters are determined based on the analytical results. The proposed control strategy with the given cyber parameters is validated for transient stability following dynamic events. Simulation results indicate that the design of a microgrid as a cyber‐physical system needs to be guided by critical values for cyber parameters to prevent system instability.